Regularities of information technology functioning (Pedagogy of Higher and Secondary Education, 2012)
Tverezovska N. T. Regularities of information technology functioningThe article describes the innovation as a prerequisite for the birth of information technology is considered, their operation is disclosed, a cyclic process of birth and decay of information technology is shown.
Keywords: innovation; information technology; cyclical; fundamental